THE PECULIARITIES OF USING THE CONCEPTS OF “PUBLIC ADMINISTRATION” AND “PUBLIC REGULATION” IN THE FIELD OF HIGH EDUCATION - Finkilshtein O.V., (Pressing Problems of Public Administration, 2015)
In the article the modern approaches to the concepts of “public administration” and“public regulation” are analyzed as the method of state influence in public administrationscience. The relevance of using these concepts to education in general and high education isconsidered. The necessity of using “public regulation” as the method of state influence isgrounded.